The concept of scarcity and its implication on human behaviour : a Qur'anic perspective - Ahmed, Wahbalbari Amir (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2009)
This paper studies the concept of scarcity in the context of conventional economics perspective and how it was developed to be the main pillar of the definition of mainstream economics. Likewise, the Islamic economists attempted to define Islamic Economics from mainstream economics perspective that relays heavily on the concept of scarcity. However, the concept of scarcity arose within the era of the rise of the secular movement that tried to exclude religion from economics, which resulted in the spread of materialism. Consequently, the concept of scarcity tends to stem from a non-religious basis as it appeared in the writings of Malthus and Robbins who advocated the concept of scarcity from its different dimensions. Nevertheless, it proved psychologically that the belief in scarcity creates the so-called scarcity mentality that perceives lack, fear and conflict which results in aggressive behavior. On the contrary, the concept of God Power that is based on the abundance mentality and is advocated by all religions conveys cooperation, trust, safety, love and results in generous behavior, which creates social intimacy among people. Moreover, this paper investigates verses from the Qur'an pertaining to the concept of God Power and the Divine rule. Finally, this research paper attempts to device a concept in the conceptual framework of Islamic Economics based on the concept of God Power that motivates the fulfillment of the Divine rule.